Study and compare the echocardiographic changes in anaemic and non-anaemic pregnant women - G., Dhivya; Grover, Suparna; Chhabra, Ajay; Goyal, Shreeji (International Journal of Research in Medical Sciences, 2025)
Background: AIM: To determine the effect of moderate to severe anaemia on the cardiovascular system of pregnant women. To compare the systolic function and diastolic function among pregnant women with moderate-severe anaemia with that of uncomplicated non-anaemic pregnant women. Methods: 30-pregnant normotensive women with moderate-severe anaemia were recruited as cases(Group A) and the controls(Group B) were 30 normotensive non-anaemic pregnant women all in 3rd trimester (26-40weeks gestation). After written informed consent, every participant underwent a 2D-transthoracic echocardiography. The parameters measured were 1) LVEDD, 2) LVESD), 3) SWTd, 4) PWTd, 5) EF 6) E/e’ and E/A ratio. Results: Mean Hb of group A participants was 7.47±1.06 g% and that of group B was 11.31±1.21 g%. Mean LVEDD of group A (4.393±0.154 cm) was higher than the group B (3.977±0.177 cm), with p value (0.0010) being statistically significant. The mean of SWTd among the group A was 1.28±0.265 cm and in group B was 1.139±0.538 cm, but their difference was not statistically significant (p value 0.2030). PWTd was significantly increased in group A (1.32±0.589 cm) than the controls (1.07±0.244 cm) with p value:0.0359. EF and Fractional shortening did not have significant difference among the two groups. The mean value of E/e’ among group A & B were, 7.42±2.1 & 7.9±2.4 respectively and the difference is not statistically significant (p value 0.4131). The E/A ratio, being an indicator of diastolic function, was higher in the cases (1.622±0.518 & 1.369±0.323 in group A & B respectively) and the difference was statistically significant (p value: 0.0269). Conclusions: LVEDD, LVESD and PWTd are all significantly increased amongst pregnant women with moderate-severe anaemia compared to pregnant women with Hb≥10g/dl. E/A ratio suggestive of diastolic dysfunction is also increased in pregnant women with anaemia but systolic functions are not affected as indicated by EF and fractional shortening.